2003
DOI: 10.1107/s0108768103007572
|View full text |Cite
|
Sign up to set email alerts
|

Structure-forming components in crystals of ternary and quaternary 3d-metal complex fluorides

Abstract: Crystallochemical analysis and classification were performed for 139 ternary and quaternary complex fluorides with the general formula M1(n)M2(m)M3F(6), belonging to 33 structure types. Using coordination sequences and the uniformity criterion the structure-forming ionic sublattices or their combinations were found, which are responsible for the formation of stable periodic frameworks. Analysis of structure-forming motifs allows the interpretation of the crystal structures of complex fluorides as close packing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Crystal structure of Li 2 ZrF 6 (C2/c, ZZ4) at 14.8 GPa. Table 2 The V VDP , R sd , S VDP , and G 3 parameters characterizing the Voronoi-Dirichlet polyhedra [16] in the structures of Li 2 ZrF 6 at atmospheric conditions (P 31m, ZZ1) [2], synthesized at 11 GPa and 1063 K (P2 1 /c, ZZ4) [9], and above 10 GPa at room temperature (C2/c, ZZ4) ( (1) They are compared with the average values for a given coordination number in all zirconium-containing fluorides at atmospheric pressure [21] (in italics). The corresponding values of the V VDP , R sd , S VDP , and G 3 parameters for all fluorides disregarding the actual coordination numbers of the zirconium atoms are 8.0(2) Å 3 , 1.24(1) Å , 23.1(8) Å 2 , and 0.082(1), respectively [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structure of Li 2 ZrF 6 (C2/c, ZZ4) at 14.8 GPa. Table 2 The V VDP , R sd , S VDP , and G 3 parameters characterizing the Voronoi-Dirichlet polyhedra [16] in the structures of Li 2 ZrF 6 at atmospheric conditions (P 31m, ZZ1) [2], synthesized at 11 GPa and 1063 K (P2 1 /c, ZZ4) [9], and above 10 GPa at room temperature (C2/c, ZZ4) ( (1) They are compared with the average values for a given coordination number in all zirconium-containing fluorides at atmospheric pressure [21] (in italics). The corresponding values of the V VDP , R sd , S VDP , and G 3 parameters for all fluorides disregarding the actual coordination numbers of the zirconium atoms are 8.0(2) Å 3 , 1.24(1) Å , 23.1(8) Å 2 , and 0.082(1), respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the ZrF K2 6 sublattice the coordination polyhedra of the Zr atoms are distorted square antiprisms, forming zig-zag chains of the in the [001] direction. Hence, to ensure a proper distribution of all the cations [21], it was assumed in the search for the lithium atoms that they would occupy the general sites 8f with the positional parameters x and y close to 0.25 and 0.5, respectively. Subsequently, a set of four voids, for which the hypothetical Li-Li and Li-Zr distances in the cationic sublattice as well as the hypothetical Li-F bond lengths were crystallographically acceptable [20,21], turned out to be the ones with the octahedral coordination to the F atoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the G 3 criterion one can choose the most significant array in a three-dimensional net. Peresypkina & Blatov (2003) have shown that the most uniform array is structure-forming, i.e. it causes a three-dimensional symmetry of the crystal structure.…”
Section: Methodsmentioning
confidence: 99%
“…From the viewpoint of crystal chemistry, this corresponds to the displacement vectors t 1 = [ 1 2 0 0] and t 2 = [0 1 2 0] applied to Sb atoms located at z = 0 and z = 1/2, respectively, in NaSbCl 6 followed by a translation of the origin t = ( 1 2 1 2 0). In hexahalides such as KSbF 6 , CaTbF 6 or NaSbCl 6 , the halide ion sublattice (Peresypkina & Blatov, 2003, and references therein) is the structure-forming one. As these sublattices are not strictly close-packed arrangements they may undergo strong distortions depending on the size, the charge and the covalency effects of the counter-cations.…”
Section: Figurementioning
confidence: 99%